Increasing Children's Preparedness, Especially Street Children By Children's Friends In Dealing With The Covid-19 Pandemic Disaster Through Educative Learning And Healing - Agus Mulyana; Kusuma Kusuma; Ernalem Bangun; Pujo Widodo; Wilopo Wilopo (CV. AFDIFAL MAJU BERKAH, 2023)
The Covid-19 pandemic is affecting all age groups from young children to the elderly. Children are a population that is included in the vulnerable group category. Through Healing and Education activities. The Jakarta Sahabat Anak Foundation seeks to reduce the impact of Covid-19 by providing direct assistance which is expected to contribute to the three main components of disaster management, namely prevention, direct response and recovery. The purpose of this study is to analyze the educative learning model and examine its implementation efforts to increase children's preparedness for the Covid-19 pandemic in order to support national resilience. The research method used is a case study qualitative method supported by data that has been obtained from observations, interviews and document studies, then analyzed, and the findings are obtained. The results of this study are that educative learning is known to be one of the tools that can increase children's preparedness in dealing with the Covid-19 pandemic. The Sahabat Anak Foundation is able to take appropriate actions to respond to the Covid-19 pandemic situation as a national disaster. Educational learning initiated by the Sahabat Anak Foundation is an activity that can help children in the process of adaptation, entertainment and learning in dealing with the Covid-19 pandemic. The results of this study can be used as material for further research with the latest data so that it is more comprehensive.